Contemporary Pediatric Palliative Care: Myths and Barriers to Integration into Clinical Care - J. Friedrichsdorf, Stefan (Current Pediatric Reviews, 2017)
At least 20 million children would benefit from Pediatric Palliative Care (PPC) annually, and 8 million children would need specialized PPC services. In the USA alone, more than 42,000 children 0-19 years died in 2013, fifty-five percent of them infants younger than 1 year. This article aims to critically review eight common assumptions, myths and barriers, which may hinder the implementation of PPC into the care of a child with advanced serious illness. Interdisciplinary PPC is about matching treatment to patient goals and is considered specialized medical care for children with serious illness. It is focused on relieving pain, distressing symptoms, and stress of a serious illness and appropriate at any age and at any stage, together with curative treatment. The primary goal is to improve the quality of life of the child and his or her family. Emerging evidence shows, that palliative care involvement results in improved quality of life as well as prolongation of life.
Keywords: interdisciplinary